#TITLE_ALTERNATIVE# - VAMONDO (NIM 13203114), RYAN
Human, as a social creature, can't grow all alone by himself without any influence from his environment. The environment is influencing him directly to his motivation within him by every interaction he has been making. The environment factor is continuously effecting his basic needs that formed the motive. The basic needs have a unique degree for every person. The motive is the driver of human actions and responses he has been giving for his life. So, there is a feedback mechanism that is happening between human and his environment. The problem that appeared is we, human, can't decide or choose the environment we are in. But today, we have been given more options to choose our environment by the internet and web technology. The purpose of this research is to build a web based application that can become a media of freedom for its users to interact by giving and taking information balancely. To reach the purpose, the writer do: 1) learn the basic of David McClelland's theory of social motive; 2) learn the web technology trends; 3) implementing a framework that can translate the social theory into web 2.0 services; 5) Implement the application in laboratory's scale. This research has concluded that: 1) people who are using this application interact based on their dominant need; 2) Although the users have been given options, they have their own preference for using the services, that shows the uniqueness of user's motive; 3) to attract people to use an application, it is not enough to just giving them a good service or product, but we need to have a lot of useful resources for them to gain something they needed or wanted.